Causes and timing of mortality and morbidity among late presenters starting antiretroviral therapy in the REALITY trial - Post, F; Szubert, A; Prendergast, A; Johnston, V; Lyall, H; Fitzgerald, F; Musiime, V; Musoro, G; Chepkrorir, P; Agutu, C; Mallewa, J; Rajapakse, C; et al. (Oxford University Press, 2018)
Background: In sub-Saharan Africa, 20%-25% of people starting ART have severe immunosuppression; ~10% die within three months. In the recently-reported REALITY randomized trial, a broad enhanced anti-infection prophylaxis bundle reduced all-cause mortality versus cotrimoxazole alone; here, we investigate in detail the contribution and timing of different causes of mortality/morbidity. Methods: Participants started ART with CD4 <100 cells/mm3; enhanced-prophylaxis comprised cotrimoxazole plus 12 weeks’ isoniazid+fluconazole, single-dose albendazole and 5-days azithromycin. A blinded endpoint review committee adjudicated events and causes of death as (non-mutually exclusively) tuberculosis, cryptococcosis, severe bacterial infections (SBI), other potentially azithromycin-responsive infections, other events, and unknown (deaths only). Results Median pre-ART CD4 was 37 cells/mm3. 225/1805(12.7%) participants died by week-48. Fatal/non-fatal events occurred early (median 4.0(IQR2.0-11.7) weeks post-ART initiation), then rates declined exponentially. 154 deaths had single and 71 multiple causes, including tuberculosis in 80(4.5%) participants, cryptococcosis 20(1.1%), SBI 33(1.9%), other potentially-azithromycin-responsive infections 23(1.3%), other events 63(3.6%) and unknown 88(5.0%). Enhanced-prophylaxis reduced deaths from cryptococcosis (p=0.03) and unknown causes (p=0.03) but not tuberculosis, SBI, potentially azithromycin-responsive infections or other causes (p>0.3). Enhanced-prophylaxis reduced incidence of non-fatal/fatal tuberculosis (p=0.007) and cryptococcosis (p=0.03), but not SBI, other potentially-azithromycin-responsive infections or other events (p>0.2). By week-48, rates were lowest (<1/100 person-years [PY]) for cryptococcosis, moderate (1-5/100PY) for tuberculosis, SBI, other potentially-azithromycin-responsive events and unknown deaths, and highest (>5/100PY) for other events. Conclusions: Enhanced-prophylaxis reduced mortality from cryptococcosis and unknown causes and non-fatal tuberculosis and cryptococcosis. High early incidence of fatal/non-fatal events highlights the need for starting enhanced-prophylaxis with ART in advanced disease.